The Economic Stabilisation Fund — An (Interim) Assessment - Philipp Steinberg; Holger Lüthen; Lukas Gehring; Daniel Schulz-Bianco (Wirtschaftsdienst)
Abstract The Economic Stabilisation Fund (ESF) is one of several German state aid instruments set up to combat the economic fallout of COVID-19. The ESF offers a range of instruments from equity to hybrid capital, including silent participation and subordinated loans. In exceptional cases, the ESF may also become a direct shareholder. While the ESF stabilised only a relatively small number of companies, it constitutes an important building block in Germany’s overall business support framework. Due to its tailor-made stabilisation measures, companies of economic significance were successfully stabilised during the pandemic.